PERAN STAKEHOLDER DALAM MENDUKUNG PERENCANAAN PEMBIAYAAN PENDIDIKAN BERBASIS MBS DI SEKOLAH DASAR - Chindytia Chindytia; Ida Bagus Gede Surya Abadi; I Made Gde Darma Sanjaya; Kadek Helsa Kirana Apsari; I Putu David Smarananda (STKIP Pesisir Selatan, 2026)
This study investigates the role of stakeholders in supporting education financing planning based on School-Based Management (SBM) principles at the elementary school level, with a focus on the challenges encountered and their implications for sustaining education quality improvement. A descriptive qualitative approach with a single case study design was conducted at SD Negeri 7 Sesetan, Denpasar. Data were collected through passive participatory observation and semi-structured interviews with eight informants, comprising the principal, teachers, school committee members, and parent representatives. Data analysis employed Miles and Huberman's model. The findings reveal that stakeholders contribute significantly in three key areas: participatory budget planning through school committee involvement in RKAS preparation, supervision and transparency of fund utilization, and community contributions in program implementation. However, stakeholder involvement remains largely formal due to limited stakeholder capacity, absent standard operational procedures for committee functions, and insufficient communication forums. Unlike prior studies focused on secondary school financing, this study specifically explores stakeholder participation dynamics at the elementary level and proposes a collaborative participatory model to build inclusive and sustainable financing governance that supports continuous education quality improvement.